A case of intraductal papillary neoplasm of the bile duct that developed 38 years after choledochoduodenostomy with invasive adenocarcinoma and lymph node metastasis - Mitsuru Kinoshita; Tadafumi Asaoka; Hidetoshi Eguchi; Takehiko Hanaki; Yoshifumi Iwagami; Hirofumi Akita; Takehiro Noda; Kunihito Gotoh; Shogo Kobayashi; Masaki Mori; Yuichiro Doki (Surgical Case Reports, 2019)
Abstract Background Intraductal papillary neoplasm of the bile duct (IPNB) is a bile duct neoplasm characterized as a precursor lesion of cholangiocarcinoma. An invasive component is present in approximately 40 to 80% of reported cases and lymph node metastasis is sometimes detected. We experienced a rare case of IPNB with invasive adenocarcinoma and lymph node metastasis that developed 38 years after choledochoduodenostomy. Case presentation A 72-year-old man presented to our hospital for liver dysfunction. The patient had a past medical history of choledochoduodenostomy for a bile duct stone 38 years previously and short bowel syndrome because of strangulation ileus 32 years previously. Ultrasonography and abdominal enhanced computed tomography (CT) revealed a left intrahepatic bile duct dilation and a papillary mass in the left hepatic duct. Positron emission tomography (PET) CT showed abnormal accumulation in the left hepatic duct and in the hepatic hilar lymph node. Endoscopic retrograde cholangiogram showed a filling defect in the left bile duct, and a cytological examination revealed the presence of atypical cells. We diagnosed cholangiocarcinoma (derived from IPNB) with lymph node metastasis and performed extended left hepatectomy, caudate lobectomy, and lymph node dissection without extrahepatic bile duct resection. Histopathological findings showed papillary adenoma and partially invasive poorly differentiated adenocarcinoma in the bile duct. Additionally, the hepatic hilar lymph node was positive. Conclusions The tumor was diagnosed as IPNB with invasive adenocarcinoma and lymph node metastasis. Biliary tract cancer that develops after choledochoduodenostomy is extremely rare, and only 17 cases (including IPNB) have been reported in the literature.